EVALUATION OF MECHANICAL PROPERTIES OF PRE-LOADED GLASS FIBER/EPOXY COMPOSITE REINFORCED WITH TiO₂ NANOPARTICLES: THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
This research investigates the combined effects of biaxial preloading and the addition of titanium dioxide (TiO₂) nanoparticles (particle size 50nm) on the mechanical characteristic of glass fiber-reinforced epoxy composites. Specimens were prepared using different weight fraction of TiO₂ (0, 1, 3, and 5%), with different preload levels (0, 400, 800, and 1200 N). The mechanical performance was evaluated through flexural, tensile, and impact tests. The results showed that the best enhancement in mechanical properties were attained at 3% weight percentage of TiO₂ with a preload of 800 N, with tensile strength increasing by 75.82%, impact strength by 127.14%, and flexural stress by 425.87% compared to the unloaded and unreinforced sample. In contrast, a performance decline was observed when the weight fraction increased to 5% with a high preload (1200 N), attributed to particle agglomeration and internal damage to the composite structure.